2010
DOI: 10.1177/1534508410379796
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Student Risk Screening Scale: An Effective Tool for Use in Diverse Urban Elementary Schools

Abstract: The authors examined the psychometric properties of the Student Risk Screening Scale, as used in three ethnically, culturally, and economically diverse urban midwestern elementary schools. The results suggest strong internal consistency (a = .81-.82) and test-retest stability (r = .86). Initial ratings of risk as measured by the Student Risk Screening Scale were statistically significant in predicting year-end office discipline referral rates and springtime oral reading fluency scores. Students with higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
6
30
0
Order By: Relevance
“…Findings were highly similar to previous short-term (1 year) predictive validity studies indicating fall SRSS-E7 scores predicted year-end behavioral outcomes (e.g., ODRs and self-control skills; Oakes et al, 2010), and academic outcomes, such as ORF (Oakes et al, 2010) and proficiency in language art skills ). Yet this is the first study at the elementary level to explore the extent to which screening scores predicted in-school suspensions and nurse visits.…”
Section: Predictive Validity Of Externalizing Scores In Elementary Scsupporting
confidence: 83%
See 1 more Smart Citation
“…Findings were highly similar to previous short-term (1 year) predictive validity studies indicating fall SRSS-E7 scores predicted year-end behavioral outcomes (e.g., ODRs and self-control skills; Oakes et al, 2010), and academic outcomes, such as ORF (Oakes et al, 2010) and proficiency in language art skills ). Yet this is the first study at the elementary level to explore the extent to which screening scores predicted in-school suspensions and nurse visits.…”
Section: Predictive Validity Of Externalizing Scores In Elementary Scsupporting
confidence: 83%
“…Findings offer additional evidence of fall SRSS-E7 scores predicting behavioral and academic year-end outcomes for elementary-age students consistent with early inquiry of the original SRSS tool (e.g., Oakes et al, 2010). Furthermore, we provide initial evidence suggesting fall SRSS-I5 scores also predict important educational outcomes for students.…”
Section: Discussionsupporting
confidence: 70%
“…ROC curves also suggest chance estimates are improved by approximately 20-30% in these domains. Previous studies at the elementary level have found SRSS scores are inversely related to year-end reading (Oakes et al, 2010) and language arts achievement. At the secondary level, SRSS scores are predictive of course failures and grade point averages (Lane, Bruhn, Eisner, & Kalberg, 2010;Lane, Kalberg, Parks, & Carter, 2008;Lane et al, 2013;Lane, Parks, Kalberg, & Carter, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Research supports the use of the SRSS-IE as a reliable and valid tool for universal screening at the elementary school level [18,20], middle school level [21], high school level [22], in early childhood settings [23] and for use with English Language Learners [24].…”
Section: Developing Local Norms For Universal Screeningmentioning
confidence: 99%